Penggunaan Alat (Airsmart): Sebagai Dehumidifier Otomatis Berbasis Mikrokontroler untuk Menurunkan Kelembapan Udara - Ahcmad Citro Demolingo; Tumartony T Hiola; Deddy Alif Utama (Poltekkes Kemenkes Semarang, 2025)
Air humidity in tropical regions such as Gorontalo City, which is generally high (above 60% RH), can promote the growth of microbial fungi, bacteria, and viruses, as well as increase the risk of respiratory diseases and material damage. This study designs and evaluates the performance of the Advanced Intelligent Relative Humidity System (Airsmart), an automatic microcontroller-based dehumidifier with a DHT22 sensor, to control humidity in real time. The method used is descriptive-analytic; measurements were taken in 36 boarding rooms at two locations (Novalinda Boarding House and Putri Gemilang Boarding House) from March 3–11, 2025. Before using Airsmart, the humidity in each room ranged from 66–83% RH, exceeding the ideal standard set by the Ministry of Health Regulation No. 2 of 2023 (40–60% RH). After operation, humidity decreased significantly to 53–59% RH, with an average reduction of 18% RH (range 10–26% RH), and all rooms (100%) met the ideal standard. These findings confirm the effectiveness of Airsmart in reducing and maintaining air humidity with precision. The application of this device is relevant for private residences, boarding houses, as well as public facilities in humid climate areas, not only enhancing thermal comfort but also reducing the risk of airborne diseases and maintaining indoor air quality. For further development, improving energy efficiency and integrating with Internet of Things (IoT) systems is recommended to expand Airsmart's performance and scope of use.